The odd life of Timothy Green [videorecording (DVD)] - Hedges, Peter; Wiest, Dianne; Garner, Jennifer, 1972-; Adams, C.J (Walt Disney Studios Home Entertainment, 2012)
When a childless couple buries a box with all of their wishes for an infant in their backyard, their wishes are granted. However, their child, Timothy Green, is not all that he appears.